Political Accountability and Regulatory Performance in Infrastructure Industries : An Empirical Analysis - Gasmi, Farid; Um, Paul Noumba; Virto, Laura Recuero (World Bank, 2012)
The relationship between the quality of political institutions and the performance of regulation has recently assumed greater prominence in the policy debate on the effectiveness of infrastructure industry reforms. Taking the view that political accountability is a key factor linking political and regulatory structures and processes, this article empirically investigates its impact on the performance of regulation in telecommunications in time-series–cross-sectional data sets for 29 developing countries and 23 developed countries during 1985–99. In addition to confirming some well-documented results on the positive role of regulatory governance in infrastructure industries, the article provides empirical evidence on the impact of the quality of political institutions and their modes of functioning on regulatory performance. The analysis finds that the impact of political accountability on the performance of regulation is stronger in developing countries. An important policy implication is that future reforms in these countries should give due attention to the development of politically accountable systems.